Contabilização da pegada hídrica azul, verde e cinza da rizicultura no perímetro irrigado Betume/SE - Brandão, Camilo Rafael Pereira (2020)
The water is a valuable and indispensable resource for the maintenance of terrestrial ecosystems, about 53% of freshwater production in the South American continent and 12% of the world total is in Brazil. Studies show that agriculture consumes 70% of the world's freshwater through the use of irrigation systems and the release of pollutants into water bodies the intensive use of agrochemicals has a direct effect on water quality, which in turn directly affects and indirectly the health, safety and welfare of the population. The concept of Water Footprint (WF) has been gaining prominence due to the importance of accounting for water use, being an important indicator for actions aimed at circumventing the effects of scarcity in the world through the quantification of its components. Considering that the state of Sergipe has a significant agricultural production within the Northeastern and Brazilian scenario it is important to know the amount of water used in the development of this activity, as well as its profitability and the use of agrochemicals in the region. This work aimed to account the Water Footprint (WF) of the green, blue and gray components in the irrigation perimeter of the Betume irrigated perimeter, located in Neópolis / SE for 2016, 2017 and 2018 through the method proposed by Arjen Y. Hoekstra with the help of FAO's CROPWAT 8.0 software, as well as getting to know the reality of local rice farmers regarding the management of agrochemicals and the profitability of rice. The results showed that WFgreen accounted for 51% (2016), 34% (2017) and 60% (2018) of all water used in the crop. The largest WFblue between the years was in 2017 (67%) and WFgray accounted for about (5%) for 2016 and (4%) for 2017 and 2018 respectively. Questionnaires were applied to the rice farmers of the region, the answers led us to the conclusion that there are no instructions and interventions from the competent agencies to guide these workers in the use of agrochemicals. Other important information was obtained from the crop profitability data, and it is possible to identify that the lack of investments by the state government to guarantee the autonomy of rice farmers in the final transfer of the hectares of harvested rice affects the generation of higher profits for the region. It is expected to contribute to the area of environmental science, starting with the management of two water resources in the São Francisco region, minimizing the social and environmental impacts caused by the handling of agrochemical and economic products in the devaluation of rice in the region.